Microscopic investigation of the use of gallium nitrate for root surface treatment in rat teeth submitted to delayed replantation - Mori,Graziela Garrido (2007)
The aim of this study was to investigate the effect of gallium nitrate solution, an anti-resorption substance, when applied for root surface treatment in rat teeth submitted to delayed replantation, in order to inhibit the root resorption process and enhance repair. For such purpose, 20 maxillary right central incisors of rats were randomly assigned to 2 groups (n=10). In group I, root surface was treated with 10-4M gallium nitrate solution for 20 min, while in group II root surface was treated with 2% sodium fluoride for 20 min. All root canals were filled with a calcium hydroxide-based paste. At 15 and 60 days after replantation, the animals were killed and the specimens were processed in laboratory for light transmission microscopy. In both groups, there was mild occurrence of ankylosis and root resorption. The connective tissue formed at the periodontal ligament area was arranged parallel to the root in most specimens in both groups and presented signs of inflammation. In group I, there was periodontal pocket formation in all specimens at 60 days, revealing lack of repair. These findings contraindicate the use of gallium nitrate for root surface treatment of teeth submitted to late replantation.